Withdrawal behavior of Malaysian Islamic bank customers: empirical evidence from three major issues - Abduh, Muhamad (International Association of Islamic Banks, 2014)
As interest is prohibited, the reliance of Islamic banking towards bank deposits from depositors is higher than conventional banking. Efforts that could help in preventing funds withdrawal by the depositors thus become necessary in order to avoid bank instability. This study is aimed at investigating factors that may influence the withdrawal behavior of Malaysian Islamic banks customers. The withdrawal behavior studied here is in conjunction with three major issues which are (i) issues of non-shariah compliance, (ii) lower returns as compared to other banks, and (iii) rumors about forthcoming financial crisis that may affect the performance of the bank. The research employed a direct survey through a self-administered questionnaire handed out to Islamic banks customers in Malaysia using the multi-stage sampling technique. The intention to avoid interest, type of account, working status, bank status, and bank ownership are the significant factors that could influence withdrawal behavior in model 1. Working status and bank ownership are the factors which influence withdrawal behavior in model 2. Lastly, for model 3, factors that emerged to be significant are type of account, total deposit in bank, awareness on deposit insurance, intention to avoid interest and perception that Islamic banks are less affected by the crisis.